The French Nuclear Challenge to EU Green Energy Governance - Andrey Baykov; Anne Crowley-Vigneau; Yelena Kalyuzhnova (Современная Европа)
This paper explores the role of nuclear power in substituting fossil fuels and contributing to the net zero. It considers to what extent the French position on nuclear energy is viable within the framework of EU green energy governance. The analysis of EU legal attempts to develop a common strategy for member countries and the case study of France reveal the controversial nature of nuclear energy. The authors argue that the EU could work towards easing off nuclear energy and could successfully overcome the pro-nuclear views of countries which currently depend on it for electricity production. The limited climate benefits of nuclear energy, when the whole life-cycle of nuclear reactors is considered, and the unease of the population with nuclear energy, even in countries that depend on it, chart a probable new course for a renewable energy mix in the EU. This phasing-out of nuclear energy is likely to be progressive so as to avoid lost investments in developing the technology and will hinge on how rapidly renewables reach their technological maturity.